Screenplay: Schedule 7 - Glenn, Elsa Marguerite Henriette (Centre for Film and Media Studies, 2016)
This creative project and essay for a Masters degree in Media Theory and Practice is focused around the design of a South African TV series called 'Schedule 7' which is set in Cape Town's south peninsula in a (fictional) non-governmental, psychiatric clinic. The premise is that a troubled handful of patients' perspectives on life change after they encounter what they believe to be God's salvation when they accidentally almost burn themselves to death. The format follows their endeavours to follow and serve God, who they term 'GOGO' (God of Goodness Only), with mixed results. The format is an hour slot comedy-drama series designed for television broadcast (in that it is structured around commercial breaks). A comprehensive series bible is included, as well as two full sample episodes: the pilot and episode 3.Accompanying the creative components, the academic research essay firstly looks at the significance of mental illness: particularly in terms of stigma, South African context and places of treatment. It argues that an NGO psychiatric clinic makes for an interesting setting for a TV series as it allows characters from a range of socio-economic backgrounds to be rendered equal in power and united under a 'patient' status. This section also looks at mental illness intersecting with religion or faith. Secondly, the essay gives an overview of trends in and significant instances of on-screen representations of mental illness for which it offers a critique. Thirdly, in light of the issues raised surrounding mental illness, religion and the strengths and weaknesses of on-screen fiction around the subject so far, it offers an explication of the creative choices made in the design of the TV series, which were made with the aim of a resulting TV series that is enjoyable, relevant, diverse, and open-ended in its exploration of both experiences of mental illness and religious perception and practice.